(3GdQjGVjGJ GdMOjKI (B:s (3GdeJLgGJ hGdYOOjGJ(B-(3GdGMOKjGJ,GdefMfjGJ hGdeYOdGJ(B-(3GdJcGed GdYOOj(B-(3GdGYOGO(B-(3bhGfjf eKdKjI (B/s - (3GHhQMeI, GTQa MSjfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2008)
(3efP GdbOe hGdQjGVjGJ JYQa HCe GdYdhe hCWdbhG YdjgG CSeGA cKjQI eKd edcI GdYdhe hbjUQI GdYdhe Edi BNQg ef GdCSeGAGdJj JHQR OhQ GdQjGVjGJ hCgejJgG hCfWdGbG ef GdCgejI GdHGdZI dgPG GdYde GdPj jONd aj LejY efGMj GdMjGI hEf gPg GdeGOI gj eJJWdH CLHGQj deYXe GdJNUUGJ aj GdLGeYGJ hGdcdjGJ abO Ve gPG GdcJGH aj WjGJg aUh QFjSjI JfGhdJ GdehGVjY GdJGdjI (B: (3GdeJLgGJ hGdYOOjGJ(B. -(3GdGMOKjGJ(B. -(3GdefMfjGJ hGdeYGOdGJ(B. -(3GdJcGed GdYOOj(B. -(3GdGYOGO (B.-(3bhGfjf eKdKjIs
(3HjHdjhZQGajG U(B.237s
Keywords: (3GdGMJeGdGJ , GdefMfjGJ hGdeYGOdGJs; (3GdQjGVjGJs